DEVELOPMENT AND EVALUATION OF IN SITU GELLING GASTRORETENTIVE FORMULATIONS OF MELOXICAM - J, Anyanwu NC; Y, Adogo L; B, Ajide (Universal Journal of Pharmaceutical Research, 2017)
Objective: The aim of this study was to develop a novel gastro retentive oral floating in situ gelling system for controlled release of Meloxicam. Meloxicam is an NSAID that inhibits cyclooxygenase (COX) synthesis and has analgesic and antipyretic effects. Methods: Four polymer based floating in situ gelling systems of Meloxicam were prepared by dissolving varying concentrations of different ingredients including sodium alginate, HPMC K100M, calcium carbonate, sodium citrate. The prepared gels were characterized for solution viscosity, pH, gelling capacity, floating lag time, floating duration and in-vitro release study. Results: The formulations possessed satisfactory pH value ranging from 7.25±0.09 to 8.12±0.49. All the formulations showed instant gelation maintaining integrity for at least 12 h. Maximum drug release was shown by formulations of batch G1 (94.38%). Conclusion: The study demonstrated that a stomach specific in-situ gel of Meloxicam could be prepared using the floating mechanism to increase the residence time of the drug in the stomach and improve bioavailability and thus improve patient compliance. Peer Review History: Received 17 April 2017; Revised 9 May; Accepted 29 June, Available online 15 July 2017 Academic Editor: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Reviewer(s) detail: Dr. Wilman Ismael Carrillo Terán , Technical University of Ambato Avda, Ecuador, wilmanct@gmail.com Dr. Maha Khalifa Ahmed Khalifa , Al-Azhar Universit - Cairo, Egypt, mahakhalifa.ahmed@hotmail.com